Ultrasensitive and reproducible SERS platform of coupled Ag grating with multibranched Au nanoparticles - Kalachyova E. Evgeniya; Mares D. David; Jerabek V. Vitezslav; Ulbrich P. Pavel; Lapcak L. Ladislav; Svorcik V. Vaclav; Lyutakov O. Oleksy (2017, 2017)
Title screen